Blue Accounting Bagi Masyarakat Laut Torosiaje - Yusuf, Nilawaty; Niswatin, Niswatin; Muhammad Fadli Mantali; Ardi Wiranata Moogangga (LPPM UBP, 2025)
This research aims to find out the implementation of Blue Accounting for the Torosiaje Sea community. To be able to answer the problem in the application of blue accounting in the Torosiaje marine community, the researcher uses a qualitative research method with a case study approach. The researcher uses stages based on accounting principles, namely identification, recognition, measurement, presentation and disclosure to measure the implementation of blue accounting. The data collection methods used are observation, interviews and documentation, and the informant chosen is the village government as the one who practices blue accounting. The results of the study found that the village government has implemented the practice of blue accounting with a budget for environmental management and a budget for improving the community's economy as well as a budget for social aspects as a goal for the sustainability of the marine ecosystem